2008
DOI: 10.1091/mbc.e07-07-0659
|View full text |Cite
|
Sign up to set email alerts
|

Global Analysis of Yeast Endosomal Transport Identifies the Vps55/68 Sorting Complex

Abstract: Endosomal transport is critical for cellular processes ranging from receptor down-regulation and retroviral budding to the immune response. A full understanding of endosome sorting requires a comprehensive picture of the multiprotein complexes that orchestrate vesicle formation and fusion. Here, we use unsupervised, large-scale phenotypic analysis and a novel computational approach for the global identification of endosomal transport factors. This technique effectively identifies components of known and novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
51
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 68 publications
7
51
0
Order By: Relevance
“…Because the principles of membrane trafficking are conserved from yeast to neurons, results obtained with HeLa cells are likely to be valid for other cell types. These features are quite similar to those of Vps55p, a member of this family expressed in S. cerevisiae, which is implicated in late endosome-to-vacuole transport (13,26). This suggests that the members of this family provide a function in membrane traffic that is common to phylogenetically distant eukaryotes.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Because the principles of membrane trafficking are conserved from yeast to neurons, results obtained with HeLa cells are likely to be valid for other cell types. These features are quite similar to those of Vps55p, a member of this family expressed in S. cerevisiae, which is implicated in late endosome-to-vacuole transport (13,26). This suggests that the members of this family provide a function in membrane traffic that is common to phylogenetically distant eukaryotes.…”
Section: Discussionsupporting
confidence: 52%
“…It functions as a regulator of TGN to apical plasma membrane traffic in the secretory pathway of polarized cells (31). Vps55p appears to be such a general regulator of the membrane traffic between endosomes and the vacuole (13,26). Our results indicate that endospanins function in endosomes.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In yeast, Vps55p and hLEPROT are localized in the late endosome and participate in the vacuolar targeting of CPY (15). Vps55p also participates in the downregulation of the pheromone receptor ste3p (16). It has been suggested that LEPROT plays a role in late endocytotic steps (17).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that LEPROT family members are part of functional protein complexes that include at least 1 small membrane protein with 4 putative transmembrane domains. Indeed, Vps55p interacts with Vps68p, a small tetraspan protein (16). Recently, it has been demonstrated in vitro that LEPROT negatively regulates leptin receptor cell-surface expression and that in vivo LEPROT silencing in mouse hypothalamic arcuate nucleus increases leptin signaling (17).…”
Section: Introductionmentioning
confidence: 99%